There is plenty of time at the bottom: the economics, risk and ethics of time compression - Sandberg, Anders (Foresight (Cambridge), 2019)
Purpose The speed of computing and other automated processes plays an important role in how the world functions by causing “time compression”. This paper aims to review reasons to believe computation will continue to become faster in the future, the economic consequences of speedups and how these affect risk, ethics and governance. Design/methodology/approach A brief review of science and trends followed by an analysis of consequences. Findings Current computation is far from the physical limits in terms of processing speed. Algorithmic improvements may be equally powerful but cannot easily be predicted or bounded. Communication and sensing is already at the physical speed limits, although improvements in bandwidth will likely be significant. The value in these speedups lies in productivity gains, timeliness, early arrival of results and cybernetic feedback shifts. However, time compression can lead to loss of control owing to inability to track fast change, emergent or systemic risk and asynchrony. Speedups can also exacerbate inequalities between different agents and reduce safety if there are competitive pressures. Fast decisions are potentially not better decisions, as they may be made on little data. Social implications The impact on society and the challenge to governance are likely to be profound, requiring adapting new methods for managing fast-moving and technological risks. Originality/value The speed with which events happen is an important aspect of foresight, not just as a subject of prediction or analysis, but also as a driver of the kinds of dynamics that are possible.